Energy Levels and Oscillator Strengths of Ca V (Journal of Atomic, Molecular, Condensed Matter and Nano Physics, 2021)
We report an extensive and elaborate theoretical study of excitation energies and radiative data for the lowest 148 fine-structure levels of Sulphur-like Ca using Configuration Interaction Method (CIV3).  We have included the relativistic effects using Breit-Pauli approximation by adding mass-correction, Darwin and Spin-Orbit terms to the non-relativistic Hamiltonian. Dipole allowed transitions are fined tuned by adjusting diagonal elements of the Hamiltonian Matrix. The exact identification of many levels becomes tedious due to the strong mixing between several fine-structure levels. We have compared our calculated values of energy with the data compiled by National Institute of standard and Technology (NIST) and found good agreement. We have reported data for many new levels which are not in the NIST database.
Keywords: Atomic structure; Excitation energies; Oscillator strengths